Quantification and Variation of Microclimatic Variables Within Tree Canopies - Considerations for Epiphyte Research - Murakami, Mariana; Nunes Ramos, Flavio; Durand, Maxime; Ashton, Robert; Batke, Sven P. (Frontiers in Forests and Global Change, 2022)
Forest canopies are incredibly complex self-maintaining biological structures. Conditions above and within the canopy can differ vastly, often resulting in a vertical gradient of microclimate conditions. Canopy epiphytic plants have to deal with climatic variability on much more variable scales compared to many other plant groups. The difficulty of sensor installation and the high costs of some of them can explain why it has been ignored in many studies on canopy epiphytes. Direct measurements of microenvironmental conditions are the only accurate way to assess specific intra-canopy environmental conditions, as there is also still a lack of methodologically and financially viable alternatives to allow the collection of this type of data. This study aimed to make recommendations for the direct use of microclimate measurements in epiphyte research and to summarize key discussion points concerning the number and placement of sensors required for different types of epiphyte studies. In addition, we presented high-resolution field data from the UK, where we employed over 56 microclimate sensors, to demonstrate the spatial and temporal variability of light, temperature, and relative humidity (RH) in a tree canopy. Our data demonstrated that some microclimate variables (e.g. temperature and RH) are more predictable in their distribution and show less variability in the canopy compared to light, which was highly variable throughout the canopy, even at a close spatial scale. We were able to demonstrate that a considerable number of sensors in our study captured only a very small quantity of variance within the canopy, indicating that fewer sensors would have been enough to capture mean conditions of light radiation, temperature, and RH, without losing too much precision. For the first time, we have made recommendations regarding the placement and number of sensors required in studies that specifically require the use of microclimate sensors in epiphyte work in forest canopies.